Methyl cap binding protein 2: a key epigenetic protein in systemic sclerosis. (20th November 2018) - Henderson, John; Brown, Max; Horsburgh, Steven; Duffy, Laura; Wilkinson, Sarah; Worrell, Julie; Stratton, Richard; O'Reilly, Steven
Abstract: Objective: SSc is an autoimmune connective tissue disease that results in skin fibrosis and currently has no effective treatment. Epigenetic modifications have been described and these may be key in initiating and driving fibroblast activation. Among these epigenetic modifications methylation may be of central importance. The aim of this study was to examine the role of methyl cap binding protein-2 (MeCP2) in SSc fibrosis. Methods: We used healthy and SSc dermal fibroblasts to examine the role of MeCP2, using both small interfering RNA silencing and lentiviral overexpression to determine its effects. We also examined the expression of MeCP2 in SSc fibroblasts by immunoblotting. miRNA132 was quantified by Taqman real time PCR. Results: We demonstrated that TGF-β1 induced the expression of MeCP2 in normal cells, and showed that SSc fibroblasts expressed high levels of MeCP2 under basal conditions. MeCP2 positively regulated the expression of extracellular matrix through epigenetic repression of the Wnt antagonist sFRP-1, leading to enhanced Wnt signalling. This mediated fibrosis through glycolysis, as the glycolysis inhibitor 2-deoxyglucose diminished the Wnt-mediated collagen expression. MiR132 expression was reduced in SSc fibroblasts. Conclusion: The results suggest that an epigenetic loop exists mediating fibrosis. Targeting of MeCP2, as a key epigenetic regulator, may be a promising therapeutic approach, as would targeting the metabolic reprogramming that occurs through aerobic glycolysis.